Liacarus (Liacarus) coracinus - Murvanidze, Maka; Cilbircioğlu, Cihan; Özdemir, Esengül; Inak, Emre (Zenodo, 2020)
Liacarus (Liacarus) coracinus (C.L. Koch, 1841) Material – One specimen in Aluç Dağı (mountain) Natural Park, Ankara, N 40° 49′ 75.37′′, E 32° 58′ 26.46′′, alt. = 1402 m, 15 July 2018, soil. Previous records in Turkey – Giresun, Mersin, Ordu and Samsun, Trabzon (Grobler et al. 2003), Kocaeli (Yaça and Baran 2019). Global distribution – Palaearctic. Ecology – Forest soils, moss, litter.

Published as part of Murvanidze, Maka, Cilbircioğlu, Cihan, Özdemir, Esengül & Inak, Emre, 2020, Checklist of oribatid mites (Acari: Oribatida) of the Central Black Sea basin of Turkey with new records for the country, pp. 255-277 in Persian Journal of Acarology 9 (3) on page 260, DOI: 10.22073/pja.v9i3.61909, http://zenodo.org/record/5236444
Keywords: Arthropoda; Arachnida; Animalia; Liacarus; Biodiversity; Sarcoptiformes; Liacaridae; Liacarus coracinus; Taxonomy; 2. Zero hunger; 15. Life on land